Integración vertical: El caso de la explotación de aeropuertos - Marcos Gallacher; Alfredo Sesé (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2006)
– The provision of airport services results in a web of contractual relationships between the main contractor and other firms. The existence of multiple services offered in airports allows several contractual alternatives to be chosen. In particular, the main contractor may choose to carry out these under his own management (vertical integration) or alternatively transfer them so they are under the control of another firm (dis-integration). The advantages of either alternatives depends on a host of factors. This paper analyzes the impact on vertical integration of: (a) difficulties in controlling labor and (b) the need for specialized knowledge on specific business processes. The paper shows that, in general, the decision to integrate a process is inversely related to the above two factors. The paper also analyzes the relevance of dis-integration as a tool for the reduction of business risks. We find that – for this industry – decisions relative to dis-integration do not appear to be justified as a tool for managing risks (income variability) of the firm.
Keywords: L2; D2; L8; 330